Finding order in slow axonal transport. (August 2020) - Roy, Subhojit
Highlights: Pulse-chase radiolabeling studies characterized fast and slow axonal transport. Fast and slow axonal transport conveys distinct, non-overlapping cargoes. Apparent coherence is seen in the transport of slow component cargoes. Live imaging indicates surprising diversity among slow transport cargoes. Slow component may convey diverse multiprotein complexes with distinct mechanisms. Slow component may depend on vesicle transport. Abstract : Slow axonal transport conveys cytosolic and cytoskeletal proteins into axons and synapses at overall velocities that are several orders of magnitude slower than the fast transport of membranous organelles such as vesicles and mitochondria. The phenomenon of slow transport was characterized by in vivo pulse-chase radiolabeling studies done decades ago, and proposed models emphasized an orderly cargo-movement, with apparent cohesive transport of multiple proteins and subcellular structures along axons over weeks to months. However, visualization of cytosolic and cytoskeletal cargoes in cultured neurons at much higher temporal and spatial resolution has revealed an unexpected diversity in movement — ranging from a diffusion-like biased motion, to intermittent cargo dynamics and unusual polymerization-based transport paradigms. This review provides an updated view of slow axonal transport and explores emergent mechanistic themes in this enigmatic rate-class.